Textbooks and Supplementary Materials in Teaching English Pronunciation - Tricsli, Karolína (Univerzita Pardubice, 2021)
This diploma thesis deals with the issue of teaching pronunciation in English lessons at a particular grammar school with a specific focus on the use of textbooks in teaching pronunciation. The theoretical part first comments on the general definition of English pronunciation with the main goal of describing pronunciation teaching. Furthermore, the theoretical part introduces the term 'textbook'. Firstly, the theory is focused generally on the textbook as a material didactic tool, then attention is then focused on the specifics of a foreign language textbook. The practical part contains a case study of English teachers at a selected grammar school. To begin with, the textbook that is used at the school is analysed with the aim of evaluating what opportunities for pronunciation teaching are offered in the textbook. Furthermore, interviews were conducted with teachers who use this textbook, with the main goal of finding out how teachers evaluate this textbook and how they use it in teaching pronunciation.
Učebnice a další materiály pro výuku anglické výslovnosti
Keywords: výslovnost; výuka angličtina; anglická výslovnost; výuka výslovnosti; učebnice; hodnocení učebnice; pronunciation; English teaching; English pronunciation; pronunciation teaching; textbook; textbook evaluation